Neonatal deaths in the 7th Health Region of the State of Paraná from 2017 to 2021 (Research, Society and Development, 2024)
Objective: To analyze the frequency of neonatal deaths and their causes in the 7th Health Region of the State of Paraná between the years 2017 and 2021. Methods: This is a retrospective ecological study carried out in the Southwest region of Paraná, in the 7th Health Region. Data was collected from the infant mortality information systems available on the national database TABNET/DATASUS. Mortality was analyzed according to the cause described in ICD-10 and the period occurring: early neonatal (0 to 6 days) and late neonatal (7 to 27 days). Results: 178 deaths were identified in the first month of life, corresponding to a mortality rate of 8.6/1000 live births. Most deaths occurred in early neonates (n= 138, 77.5%). Most deaths occurred because of conditions originating in the perinatal period, both for early neonates (73.2%) and late neonates (65.0%). Conclusion: There was a mortality rate of 8.6/1000 live births in the period from 2017 to 2021, and conditions in the neonatal period are the leading cause of neonatal deaths in the 7th Health Region of the State of Paraná.